Coexpression of androgen receptor and FOXA1 in nonmetastatic triple-negative breast cancer: ancillary study from PACS08 trial. (August 2015) - Guiu, Séverine; Charon-Barra, Céline; Vernerey, Déwi; Fumoleau, Pierre; Campone, Mario; Spielmann, Marc; Roché, Henri; Mesleard, Christel; Arnould, Laurent; Lemonnier, Jérôme; Lacroix-Triki, Magali
Aim: Microarray studies identified a subgroup of molecular apocrine tumors (estrogen receptor [ER] negative/androgen receptor [AR] positive) that express luminal genes including FOXA1 . FOXA1 may direct AR to sites normally occupied by ER in luminal tumors, inducing an estrogen-like gene program that stimulated proliferation.Materials & methods: Expression of AR and FOXA1 was evaluated by immunohistochemistry in 592 patients with nonmetastatic triple-negative breast cancer (TNBC).Results: Coexpression of AR and FOXA1 was found in 15.2% of patients. These tumors were more frequently lobular, found in older patients and exhibited a lower nuclear grade and a greater degree of node involvement. They less often exhibited lymphocytic infiltrate, pushing margins, syncytial architecture, central fibrosis or necrosis.Conclusion: TNBC with coexpression of AR and FOXA1 seems to behave like luminal tumors with a morphological profile distinct from other TNBC. These biomarkers could be useful to identify a subgroup of TNBC and could have future therapeutic implications.